PERSPEKTIF HUKUM PIDANA INDONESIA DAN HUKUM PIDANA ISLAM TERHADAP TINDAK PIDANA KORUPSI - Kasim, Zainuddin (JURNAL RISET INDRAGIRI, 2024)
Corruption is a serious problem in Indonesia, undermining the country's social, economic and political order. The government has attempted to enforce laws related to corruption, but this crime is still rampant. This research discusses the perspectives of Indonesian criminal law and Islamic criminal law on corruption, with the aim of understanding how the two legal systems address corruption and the extent to which they can complement each other in law enforcement. In Indonesian criminal law, corruption is categorized as an extraordinary crime. Based on Law No. 31 of 1999 jo Law No. 20 of 2001, various types of corruption have been formulated and imposed sanctions such as death penalty, imprisonment, fines, and other additional penalties. However, the public still considers the existing sanctions to be too light. In Islamic criminal law, corruption is considered a violation of the Shari'a that aims to realize the benefit of mankind. Islam regulates the acquisition and spending of wealth with strict prohibitions against offenses such as fraud, usury, treason, and corruption. Sanctions are applied through the ta'zīr approach which is flexible and left to the government to determine. This research found that both legal systems have the potential to complement each other in enforcing the law on corruption in Indonesia. A firmer and more comprehensive application of the law is needed to overcome the problem of corruption that has taken root in Indonesian society.